1786. Safety, Efficacy, and Clinical Impact of Penicillin Allergy Skin Testing in Immunocompromised Cancer Patients at a Comprehensive Cancer Center. (26th November 2018) - Artau, Annette; Taremi, Mahnaz; Foolad, Farnaz; Berlin, Sheila; White, Candice; Mulanovich, Victor; Raad, Issam; Adachi, Javier
Abstract: Background: Patients reporting penicillin (PCN) allergies often receive alternative antibiotic therapy associated with significant health and economic disadvantages. The use of penicillin allergy skin testing (PST) to rule out PCN allergies is safe and effective in immunocompetent patients, yet data in immunocompromised patients are limited. Methods: A quality improvement process using PST to clarify PCN allergies and guide antibiotic therapy was implemented at MD Anderson Cancer Center (April–October 2017). Patients admitted to Leukemia and Genitourinary Medical Oncology (GUMO) services with a history of Type 1 reactions to PCN were eligible. Results: A total of 218 consecutive patients with reported PCN allergies were screened; 100 met inclusion criteria, were consented, and underwent PST (67 Leukemia, 33 GUMO). Sixty-one percent of tested patients reported cutaneous reactions, and 79% reported reactions >20 years ago. The most common reported allergy was to penicillin V/G (64%). Forty-eight percent were on steroids and 49% were on immunosuppresive therapy at the time of PST. For leukemia patients the median absolute neutrophil count was 0.78 (0–64.88 K/μL) and absolute lymphocyte count was 0.81 (0–116.71 K/μL). Ninety-five percent patients tested negative for PCN allergy and 4% were positive (three Leukemia, one GUMO). One test was indeterminate (negative histamine control). After PST, 25 of 67 (37%) patients receiving antibiotic therapy were changed to PCN-based antibiotics (PBA) (Figure 1). During the follow-up period (median: 177; range: 3–316 days), 65 patients who tested negative were readmitted (total 185 readmissions) and PBAs were prescribed in 58 of those readmissions (Figure 2). The most common indications for PBAs included neutropenic fever, pneumonia, and bacteremia. No patients given PBAs after negative PST experienced allergic reactions. Conclusion: PST is safe and effective to rule out PCN allergies in immunocompromised patients, with 95% of patients testing negative for PCN allergy, suggesting that patient-reported allergy is unreliable. The rate of negative tests is comparable to data in immunocompetent patients. The use of PST in cancer patients allows for optimization of antimicrobial therapy and stewardship, which is vital in this patient population at increased risk for infections and infectious complications. Disclosures: M. Taremi, ALK-Abello: Educational grant recipient, Educational grant.